Analisis Kesiapan Guru Dalam Mengimplementasikan Kurikulum Merdeka di SMA N 7 Bungo Kecamatan Tanah Sepenggal Lintas Kabupaten Muaro Bungo Provinsi Jambi - Gusnita Sriwulandari; Slamet Rianto; Nila Afryansiah (Horizon, 2023)
This study aims to obtain data, process, analyze and discuss the analysis of teacher readiness in implementing the independent curriculum in Muara Bungo district, Jambi province, seen from: 1). how is the readiness of teachers in implementing the independent curriculum 2). what are the obstacles in implementing the independent curriculum. This type of research is descriptive qualitative, the population in this study are teachers who teach at SMAN 7 Bungo using the independent curriculum, namely 28 teachers, in this study using a total sampling technique, observation data collection techniques, interviews, documentation and instruments as well as analysis techniques descriptive data analysis techniques using a Likert scale, data reduction, data presentation and conclusions. The final results of this study reveal that: 1) The readiness of teachers in implementing the independent curriculum at Bungo 7 High School is in the ready category with a percentage (64.70%). The indicators include the readiness to implement the USBN replacement assessment, the readiness for the AKM plan (minimum competency assessment) and the UN replacement character survey, the readiness to prepare a concise module format and the readiness to implement PPDB zoning 2) Obstacles in implementing the independent curriculum at SMAN 7 Bungo are among them. schools that do not have adequate facilities, teachers experience problems such as facilities, infrastructure, and limited knowledge of technology, some teachers have difficulty learning or utilizing basic skills for learning in the digital era, such as how to use Microsoft Word, make interesting and entertaining presentations, and other. as well as the lack of training in the independent curriculum or the lack of learning experience regarding the independent curriculum.